The REGIONAL FINANCIAL RATIO ANALYSIS AS PERFORMANCE APPRAISAL TOOL (CASE STUDY ON BPPKAD MAGETAN REGENCY) - Dwi Koerniawati (Jurnal Ekonomi, 2023)
This study aims to determine the financial performance of BPPKAD Magetan Regency by analyzing the ratio of regional financial independence, effectiveness and efficiency ratio, activity ratio, growth ratio, and debt service coverage ratio. This study uses secondary data for 2018-2020 obtained through financial statement analysis. The writing methods used are description and exposition. The results showed that the independence ratio is still low with an average of 28.67% but continues to increase every year. The effectiveness ratio tends to be effective with an average of 108.46% while the efficiency ratio is already efficient with an average of 4.75%. In the ratio of BPPKAD activities, Magetan Regency is still prioritized for routine expenditure (Operations) of 69.64% rather than for development expenditure (Capital) of 14.74%. The growth ratio is showing a negative trend. Thus, the financial performance of BPPKAD Magetan Regency based on regional financial ratio analysis is quite good.